Error estimates for the unilateral buckling critical load of a thin plate - Ayadi, Mekki (European Journal of Computational Mechanics, 2007)
The paper deals with error estimates for the unilateral buckling critical load of a thin plate in presence of an obstacle. First, using the Kirchhoff-Love’s plate model, an abstract error estimate is given up. Its drawback is that it contains a hard term to evaluate. Then, by using the Mindlin’s plate model together with a finite elements scheme of degree one, an error estimate, depending on the mesh size h, is established. The last part of the paper is devoted to some numerical results in order to validate the error estimate formula.